Hemispheric asymmetry in high-energy phosphate consumption during sleep-deprivation is balanced by creatine - Gordji-Nejad, Ali; Matusch, Andreas; Kleedörfer, Sophie; Patel, Harshal Jayeshkumar; Drzezga, Alexander; Elmenhorst, David; Binkofski, Ferdinand; Bauer, Andreas (Frontiers in Neuroscience, 2025)
The human brain exhibits asymmetric hemispheric activity at night; this plays a crucial role in cognitive impairment from sleep deprivation. Although there have been many investigations on this topic, there are no studies on hemispheric differences in the consumption of high-energy phosphates (HEP). We present here a new data analysis of our previously published study in which subjects were measured for changes in high-energy phosphate (HEP), tCr/tNAA, and Glu/TNAA during subacute sleep deprivation (21 h) and cognitive tests. In our new analysis, we investigated differences and asymmetries in the metabolic consumption of both hemispheres. Comprehensive per-individual voxel-wise interhemispheric comparisons at all time points and conditions showed a greater decrease from baseline of ATP in the right than in the left hemisphere. Partial volume correction yielded an apparent higher decline of PCr/Pi in gray versus white matter. We also investigated whether creatine supplementation, which has been shown to prevent cognitive impairment during sleep deprivation, affected this hemispheric asymmetry. In a second session, the subjects took a high single dose of creatine monohydrate suspension (0.35 g/kg) after baseline measurements. Creatine balanced the sleep deprivation-induced asymmetry to a higher degree in the left hemisphere, which was due to an increase in PCr/Pi and decrease in ATP. Our results confirm—via the observed decrease in ATP level—a night-active right hemisphere. Creatine administration balanced this asymmetry.